Effects of high intensity/low volume and low intensity/high volume isokinetic resistance exercise on postexercise glucose tolerance - Miller, A. D.; Ruby, B. C.; Laskin, J. J.; Gaskill, S. E. (The Journal of Strength and Conditioning Research, 2007)
The purpose of this study was to determine the effects of high intensity/low volume (HILV) and low intensity/high volume (LIHV) isokinetic resistance exercise on postexercise glucose tolerance. Subjects (n = 10) participated in a counterbalanced, randomized design of 2 separate isokinetic resistance exercise trials (HILV and LIHV) of reciprocal concentric knee flexion and knee extension in a fasted state. Each bout was followed by a 45-minute oral glucose tolerance test (OGTT; 1.8 g/kg fat free mass). Blood samples were obtained every 15 minutes to determine glucose and insulin concentrations. There was no difference in total work between the 2 trials (p = 0.229). Blood glucose was significantly higher at all time points compared with time 0 following the LIHV trial (p < 0.05). Following the HILV trial, blood glucose was significantly elevated at 15 and 30 minutes (p < 0.05), but returned to resting values by 45 minutes. Insulin concentration was significantly elevated following both trials at all time points (p < 0.05). Blood glucose and insulin were significantly higher following the LIHV at 30 and 45 minutes compared with the HILV trial (p < 0.05). These results demonstrate that although the total work output was similar across trials, high intensity muscle contraction is associated with an enhanced normalization of glucose homeostasis following a large postexercise oral glucose feed.